(untitled) (Web of Teachers: Inderscience Research, 2025)
This research explores the use of irony as a literary device in English and Uzbek literary texts. The study examines how irony is employed to convey implicit meanings, critique social norms, or highlight contradictions in character or plot. By comparing representative works from both literatures, the analysis identifies cultural, linguistic, and stylistic similarities and differences in the use of irony. The findings reveal that while irony serves similar narrative functions in both traditions, its expression is influenced by each culture’s unique worldview and literary conventions.